Value chains and food in the days of COVID-19. An exploratory research on short supply chains in Italy - Corrado, Alessandra; Fama, Marco (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2021)
The debate on the impact that the COVID-19 pandemic has had on the agri-food system is animated by contrasting positions. While some authors tend to emphasize the great resilience shown by food chains at a global level, others argue that the pandemic is exacerbating the contradictions that characterize the industrial agri-food system. The article aims to contribute to this debate by analyzing the effects of the pandemic on the Italian agri-food system. The authors analyze the way the pandemic crisis has affected the diverse agri-food chains, particularly focusing on short supply chains. Short supply chains are generally portrayed as a valid alternative to the dominant agri-business model, although more needs to be learned about their actual strengths and weaknesses. The pandemic provides an opportunity to test whether short supply chains are able to react to a global shock. It also serves to shed light on the factors that may affect, both positively and negatively, the capacity of short supply chains to address ongoing transformation of the "environmental and corporate" food regime. Starting from this assumption, the article presents the results of qualitative research exploring the reactions that short supply chains displayed to cope with the problems that emerged in the aftermath of the pandemic outbreak. As the authors show, the pandemic has highlighted some weaknesses of short supply chains. At the same time, these supply chains have also shown a great resilience and capacity for innovation. In any case, the pandemic has provided important indications to be considered at a policy level.